WORKSHOP PENGENALAN KESELAMATAN KESEHATAN KERJA (K3) MENGHADAPI ERA INDUSTRI 4.0 DI SMK NURUL ISLAM GRESIK - Suparno Suparno; Muhammad Hafidz Yusuf; Moh. Ririn Rosyidi; Iksan Iksan (UNIVERSITAS PGRI MADIUN, 2025)
Abstract. Occupational Safety and Health (OSH) is crucial for preventing workplace accidents in industrial environments. Through a Community Service activity at SMK Nurul Islam Gresik, this program aimed to instill an early understanding of the importance of OSH among students, particularly during activities in the machining workshop, which serves as a miniature version of the real working environment. The methods used in this activity included delivering OSH materials through direct presentations, practicing the use of personal protective equipment (PPE), as well as conducting discussion and Q&A sessions to assess the students' understanding of the material presented. The results of the activity showed that students were able to grasp the basic concepts of OSH, as evidenced by their active participation in discussions and their correct use of PPE during practice sessions. In conclusion, early introduction to OSH through an interactive approach effectively enhances students awareness and understanding of the importance of workplace safety in the workshop environment. Abstrak. Keselamatan dan Kesehatan Kerja (K3) penting untuk mencegah kecelakaan kerja di lingkungan industri. Melalui kegiatan Pengabdian kepada Masyarakat di SMK Nurul Islam Gresik, kegiatan ini bertujuan menanamkan pemahaman tentang pentingnya K3 kepada siswa sejak dini, khususnya saat beraktivitas di workshop permesinan yang merupakan miniatur dunia kerja sebenarnya.Metode yang digunakan dalam kegiatan ini meliputi penyampaian materi K3 secara langsung melalui presentasi, praktik penggunaan alat pelindung diri (APD), serta sesi diskusi dan tanya jawab untuk mengukur pemahaman siswa terhadap materi yang disampaikan.Hasil dari kegiatan ini menunjukkan bahwa siswa mampu memahami konsep dasar K3, terbukti dari keaktifan mereka dalam diskusi dan ketepatan penggunaan APD saat praktik.Kesimpulannya, pengenalan K3 sejak dini melalui pendekatan interaktif efektif meningkatkan kesadaran dan pemahaman siswa tentang pentingnya keselamatan kerja di lingkungan workshop.